Objects, Events, and Property-Instances - Riccardo Baratella (Baltic International Yearbook of Cognition, Logic and Communication, 2019)
The theory of events as property-instances has been considered one of the most widely accepted metaphysical theories of events. On the other hand, several philosophers claim that if both events and objects perdure, then objects must be identified with events. In this work, I investigate whether these two views can be held together. I shall argue that if they can, it depends on the particular theory of instantiation one is to adopt. In particular, I shall conclude that the theory of events as property-instances and the view that identifies objects with events can be held together only if instances of eventive universals are temporal parts of objects – namely, those temporal parts that have the universals in question.